(untitled) (INTI Nusa Mandiri, 2019)
Repeater Sales Information System is a management information system that produces various information that can be useful to support sales activities at PT. Picotel Nusantara. The manifestation of the development of the Repeater’s sales information system is the making of computer applications that are able to represent the whole designed information system. Produced sales information system applications are able to manage sales data, which includes sales transactions, cash receipt transactions, item data, data purchase orders, account data, and customer data in an organized manner, and produce complete, accurate and always current reports for each level of management . In writing this final assignment, the author uses the waterfall methodology, in this method there are several stages, namely the survey stage, the system design stage, the coding stage, the testing stage, the maintenance stage. From the method that I use, the authors build applications that can be used for the sales process, as well as promotions to customers, so that this application can be expected to be implemented by PT. Picotel Nusantara. The information system approach method used in this information system uses object-oriented methods (object oriented) which emphasize problem solving software based on objects. The system design uses Java and the database design uses MySql Server. The results of the design of sales information system applications show that the role of computer applications in information systems is very important as a support in improving the quality of sales and service activities in the company environment.